The Influence of Competitive Advantage, Market Orientation, and Partnerships on Reddoorz's Marketing Performance - Neno, Yohanes Robinsius; Miswanto, Miswanto; Siregar, Baldric; Biyanto, Frasto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this study is to evaluate the impact of competitive advantage, market orientation, and partnerships on the marketing performance of RedDoorz, a rapidly growing budget accommodation platform in Indonesia. Using a quantitative approach, primary data were collected through questionnaires distributed to 40 selected respondents using a purposive sampling technique. Based on multiple linear regression analysis, the findings indicate that competitive advantage and partnerships have a positive and significant influence on marketing performance, while market orientation does not show a significant effect. Theoretically, this study supports the resource-based view theory and serves as a reference for future research in this area. Practically, the findings can be utilized by RedDoorz management to formulate strategies aimed at enhancing competitiveness and marketing performance amidst increasingly intense competition.